The lure of political friendship: aspects of Aristotle’s philia politike in the search for a civic vinculum - Murray Faure (Acta Academica, 2010)
This article explores the idea of political friendship and, in particular, Aristotle’s notion of philia politike. The former is usually frowned upon in the public domain and the latter is often misunderstood in scholarly circles. The article is confined to an explication of philia politike and its viability for the liberal state, given the paradox that such a state cannot retain its liberal character neither with nor without an account of the good life and moral virtue. The article attempts to ascertain whether political philosophy can conceive of a civic vinculum or citizen bond without recourse to bonds such as family, ethnicity, race, nation, the Volk, religion, or a shared origin of humanity.